The role of TIRR in DNA damage and repair - Ketley, R (2022)
The integrity of our DNA genetic code is constantly under threat from a variety of different endogenous and exogenous sources. Failure to accurately repair damage to our DNA can lead to the development of diseases such as cancer. In order to maintain genomic stability, cells possess a network of highly regulated cellular processes which act together to repair DNA, known as the DNA damage response. Many different factors contribute to the repair of DNA lesions, including different proteins and RNA species. A central player in the repair of DNA double strand breaks, a particularly toxic type of DNA damage, is a protein known as 53BP1. The recruitment of 53BP1 to double strand breaks is a highly regulated process, and 53BP1 is constitutively bound by the inhibitor protein TIRR. When a double strand break occurs, TIRR and 53BP1 dissociate, allowing 53BP1 to engage chromatin at the break and function in repair. In Chapter 3 of this thesis, we explore the mechanism of this dissociation, identifying a role for RNA which is transcribed at double strand break itself. We also further characterise the role of TIRR in the wider DNA damage response, firstly in Chapter 4, where we explore the function of TIRR RNA binding in the regulation of RNA processing, and in Chapter 5, where we perform a proximity labelling experiment to identify novel interactors of TIRR. Taken together, this thesis characterises the function of the DNA repair factor TIRR, both as a 53BP1 negative regulator, and as an RNA-binding protein.